DIGITAL MARKETING UNTUK MENINGKATKAN PENJUALAN DAN MEMPERTAHANKAN USAHA - Indradewi; Situmorang, Dokman Marulitua (Mount Hope Management International Journal, 2023)
The Covid-19 pandemic has an impact on the continuity of a business's sales system. The sales system which was initially carried out with direct sales between sellers and buyers is starting to shift to the online realm. Budding entrepreneurs use online food delivery services as an initial strategy to continue operating during the pandemic. This research aims to find out how effective the use of online food delivery services is in Denpasar City, especially at Kedai Sosis Peguyangan. It is hoped that this research will provide an overview to novice business people regarding technological developments, in this case online food delivery services, as an effort to understand changes in consumer behavior in meeting food needs. The owner of the Peguyangan Sosis Shop was the subject of this research. Grab-Food and Go-Food online food delivery services are the choice of the owner of Kedai Sosis Peguyangan as a partner in operating his business. This research uses descriptive qualitative research methods with data collection techniques carried out by observation and in-depth interviews. This research shows that using online food delivery services in running a business, especially during the Covid-19 pandemic, has a positive impact on increasing sales profits and product diversification.